Comparison Between Isovolumic Acceleration and Conventional Echocardiograhic Parameters in Detecting Early Right Ventricular Systolic Dysfunction in Patients with Mitral Stenosis - rashid, Khandaker Harun or; Adhikary, Dipal Krishna; Banerjee, Sajal Krishna; Parvin, Tanjima; Md Jamil, Abu Baqar; Hossain, Md Tufazzal; Das, Mrinal Kanti; Hasan, ATM Iqbal; Sultan, Md Ashraf Uddin (University Heart Journal, 2022)
Aim: The aim of the study was to determine if the tissue Doppler imaging (TDI)-derived myocardial acceleration during isovolumic contraction (IVA) of tricuspid lateral annulus could be used in early detection of RV systolic dysfunction in patients with mitral stenosis (MS), before the clinical signs of systemic venous congestion occur and to compare between IVA and conventional echocardiographic parameters in detecting early RV systolic dysfunction in patients with MS . Methods: Ninety-six patients with severe rheumatic MS without relevant regurgitation were enrolled in the study. Conventional echocardiographic parameters (mitral valve area, transmitral diastolic gradients, pulmonary artery pressure, RV fractional area change, pulmonary flow acceleration time, tricuspid annular plane systolic excursion) and TDI-derived systolic velocities of tricuspid annulus (isovolumic myocardial acceleration: IVA, peak myocardial velocity during isovolumic contraction: IVV, peak systolic velocity during ejection period: Sa and RV MPI) were recorded from all patients. Results: TDI-derived IVA, IVV, Sa were significantly decreased in patients with MS and RV MPI is increased in patients with MS. IVA was the only parameter which had a significant negative correlation with the traditional echocardiographic parameters and RV Tei index in patients with MS. Conclusion: TDI-derived right ventricular IVA may be used as an adjunctive, reliable, noninvasive parameter for the early detection of right ventricular systolic dysfunction in patients with MS but without signs of systemic venous congestion. RV IVA negatively correlate with RV MPI, positively correlate with IVV and Sa. RV IVA shows positive correlation with RVFAC and negative correlation with PAP, LA size. IVA shows no correlation with TAPSE. University Heart Journal 2022; 18(2): 80-86